Human ACE2 Genetic Polymorphism Affecting SARS-CoV and SARS-CoV-2 Entry into Cells - Takanari Hattori; Takeshi Saito; Kosuke Okuya; Yuji Takahashi; Hiroko Miyamoto; Masahiro Kajihara; Manabu Igarashi; Ayato Takada (Microbiology Spectrum, 2022)
ABSTRACT Severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2 have a single envelope glycoprotein (S protein) that binds to human angiotensin-converting enzyme 2 (ACE2) on the host cell membrane. Previous mutational scanning studies have suggested that some substitutions corresponding to single nucleotide variants (SNVs) in human ACE2 affect the binding affinity to the receptor binding domain (RBD) of the SARS-CoV-2 S protein. However, the importance of these substitutions in actual virus infection is still unclear. In this study, we investigated the effects of the reported ACE2 SNV substitutions on the entry of SARS-CoV and SARS-CoV-2 into cells, using vesicular stomatitis Indiana virus (VSIV) pseudotyped with S proteins of these coronaviruses (CoVs). HEK293T cells transfected with plasmids expressing ACE2 having each SNV substitution were infected with the pseudotyped VSIVs and relative infectivities were determined compared to the cells expressing wild-type ACE2. We found that some of the SNV substitutions positively or negatively affected the infectivities of the pseudotyped viruses. Particularly, the H505R substitution significantly enhanced the infection with the pseudotyped VSIVs, including those having the substitutions found in the S protein RBD of SARS-CoV-2 variants of concern. Our findings suggest that human ACE2 SNVs may potentially affect cell susceptibilities to SARS-CoV and SARS-CoV-2. IMPORTANCE SARS-CoV and SARS-CoV-2 are known to cause severe pneumonia in humans. The S protein of these CoVs binds to the ACE2 molecule on the plasma membrane and mediates virus entry into cells. The interaction between the S protein and ACE2 is thought to be important for host susceptibility to these CoVs. Although previous studies suggested that some SNV substitutions in ACE2 might affect the binding to the S protein, it remains elusive whether these SNV substitutions actually alter the efficiency of the entry of SARS CoVs into cells. We analyzed the impact of the ACE2 SNVs on the cellular entry of SARS CoVs using pseudotyped VSIVs having the S protein on the viral surface. We found that some of the SNV substitutions positively or negatively affected the infectivities of the viruses. Our data support the notion that genetic polymorphisms of ACE2 may potentially influence cell susceptibilities to SARS CoVs.